Actor-network theory and the empirical critique of environmental law: unpacking the bioprospecting debates - Emilie Cloatre (Edward Elgar Publishing, 2017)
In recent years, actor-network theory (ANT), and the work of Bruno Latour in particular, have gained significant interest amongst legal scholars. This approach, derived from Science and Technology Studies (STS) and bearing various links with anthropology and ethnographic methods, has enabled new insights to emerge in relation to the ways in which law operates in everyday practices. The innovative position the approach suggests has been largely based on the breaking down of the dichotomy between nature and society, humans and non-humans, and in turn on an emphasis on the importance of materiality in social practices (and its complexity). In his early work, Bruno Latour therefore laid out the foundations of what was to become a radical rethink of sociological assumptions, by challenging the extent to which humanity can ever be imagined as being fundamentally separate from nature. Consequently, he argued that some of the most fundamental assumptions of modernity, about how knowledge is made, societies are built, and humans can relate to their environment, are mistaken and in need of revisiting. Given its deep engagement with our relationship with nature, and its grounding in the sociology of science, it is somehow surprising that ANT has not been more frequently explored in environmental law - in spite of a few examples. However, more resources are available to those wanting to imagine what an 'ANT approach to environmental law' may look like, if engaging with STS and the anthropology of science literature that has in recent years aimed to unpack some of the legal stories that surround environmental practices. In this chapter, I seek to bring together some of this scholarship to reflect on what ANT can bring to environmental law research. The chapter is illustrated specifically with the example of the use of natural resources for industrial purposes, and the long-standing debates on 'biopiracy' that have animated much legal debate since the 1990s. Through this example, I retrace the difficulty for modern environmental law to engage with practices that challenge the boundaries between nature and humanity, and the dichotomies on which law has so far operated. I explore how studies that have embraced some of the more radical claims of ANT and STS, and engaged ethnographic analyses of social practices, have illustrated how law often fails to seize the messiness of the entanglement of nature and society. I conclude by discussing how ANT, and the work of Bruno Latour, can be used more broadly by environmental lawyers seeking to reimagine the ways in which law relates to nature.